EFFECT OF SERVICE QUALITY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AND LOYALTY - Mahsyar, Syariful; Surapati, Untung (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The rapid growth of food business in Indonesia also leads to increased competition. Restaurants should have the advantage of being able to compete in order to survive and win the competition in this food business. One way that can be used to achieve such excellence is to implement the right quality of service and product quality so as to improve customer satisfaction and create consumer loyalty. This research aims to analyse the impact of service quality and product quality on customer satisfaction and the customer loyalty in restaurants and to know which factors are influential in the restaurant. In the data collection, researchers spread the questionnaire to 50 respondents who were consumers of the restaurants in Samarinda. This research Data is obtained from the results of the distribution of questionnaires through a questionnaire that is further analyzed by using path analysis, boostraping and pls alogaritma. The equation Model is processed using the SmartPLS application version 3. The result of this research is that the quality of service has no significant effect on customer satisfaction, product quality has significant effect on customer satisfaction, and customer satisfaction has significant effect on consumer loyalty.